2001
DOI: 10.1007/s003300000712
|View full text |Cite
|
Sign up to set email alerts
|

A new liposomal liver-specific contrast agent for CT: first human phase-I clinical trial assessing efficacy and safety

Abstract: In this first clinical trial liposome-encapsulated iodixanol, CT particles (CTP) were studied. The aims of the present trial were to assess the efficacy of CTP in CT and to determine the safety of different doses of CTP. A total of 47 healthy volunteers were enrolled in the present study. The CTP was administered at doses 10, 30, 70 and 100 mg encapsulated I/kg bw. Efficacy was assessed using single-slice CT of the abdomen and evaluated by dose-response attenuation curves over time in liver, spleen, and abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…In contrast, smaller liposomes are able to circulate in the blood pool for a prolonged period of time. Most liver-specific (i.e., large) liposomes cover the range from 300 to 500 nm (Desser et al, 1999;Leander et al, 2001). Blood-pool liposomes were found to need sizes from 100 to 200 nm (Sachse et al, 1997;Leike et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, smaller liposomes are able to circulate in the blood pool for a prolonged period of time. Most liver-specific (i.e., large) liposomes cover the range from 300 to 500 nm (Desser et al, 1999;Leander et al, 2001). Blood-pool liposomes were found to need sizes from 100 to 200 nm (Sachse et al, 1997;Leike et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Although liver enhancement occurred rapidly after injection, blood-pool enhancement was brief. Leander (Leander et al, 2001) performed a phase I study with liposomal iodixanol investigating doses of 10, 30, 70, and 100 mg of encapsulated I/kg. The liposomes were efficacious in enhancing hepatic and splenic tissues and in early imaging of abdominal vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Several liposomal contrast agents have previously been investigated (6)(7)(8)(9)(10)(11), since a liposome, a kind of particle, encapsulating an iodinated contrast agent is taken up by Kupffer cells or RES and allows contrast enhancement to be sustained for several minutes to several hours, which provides an advantage over conventional extracellular contrast media for liver imaging (12). A clinical trial in 2000 reported using a serine-modified liposomal contrast agent (10 Kuppfer cell-targeting technology using liposome has been exploited and Kawakami et al recently reported mannose receptor-mediated high transfection activity in liver macrophages in vivo (13). Macrophages are known to express large numbers of mannose receptors on their surface as well as serine receptors (14).…”
mentioning
confidence: 99%
“…A hurdle for novel molecular entities is the absence of historical knowledge to help guide their development and focus on specific risks. As an example, a liposomal agent based on iodine showed no adverse effects at 10–30 mg I/kg, but there were issues at 70–100 mg I/kg in a phase-I clinical trial[213]. Lack of historical data raises the burden of proof required to demonstrate safety.…”
Section: General Biological and Regulatory Hurdlesmentioning
confidence: 99%